Dwellings of the Medieval City of Ani. Historiography and Research Results - Baeva, Olga V.; Kazaryan , Armen Yu. (Actual Problems of Theory and History of Art, 2022)
The settlement of Ani is one of the most significant monuments of Eastern Christian medieval architecture, which were developing at the crossroads of cultural traditions for five centuries. Deserted at the end of the 14th–15th centuries, this large city, once the capital of the Armenian kingdom, has preserved archaeological evidence of several cultural layers. This determined the considerable interest of the researchers in the comprehensive study of the settlement of Ani, which was initiated by excavations led by N. Y. Marr, conducted in the late 19th – early decades of the 20th centuries. Residential buildings were also in the field of attention of the expedition participants. Emphasizing certain successes achieved by pre-revolutionary and Soviet historiography, the authors of the article note their natural limitations associated with the lack of new archaeological information and the long absence of the possibility to explore the already known architectural monuments in natural environment. The article proposes the periodization of the historiography of Ani dwellings, identifies and analyzes the results of studying the evolution, typology, and stylistics of the dwelling architecture of Ani, and raises questions about the degree of the elaboration and discussion of architectural issues in different types of residential quarters, streets, and buildings. The study has been realized by the grant of the Russian Science Foundation, project no. 22-18-00354, in the Moscow State University of Civil Engineering (MGSU), National Research University.